Role of hsp20 in the Production of Spores and Insecticidal Crystal Proteins in Bacillus thuringiensis - Xie, Junyan; Peng, Jinli; Yi, Zixian; Zhao, Xiaoli; Li, Shuiming; Zhang, Tong; Quan, Meifang; Yang, Shuqing; Lu, Jiaoyang; Zhou, Pengji; Xia, Liqiu; Ding, Xuezhi (Frontiers in Microbiology, 2019)
The small heat shock protein plays an important role in response to stresses. We wanted to investigate how Hsp20 affects sporulation and production of insecticidal crystal proteins (ICPs) in Bacillus thuringiensis (Bt) at the stationary growth phase when cells are starved. The hsp20 gene was knocked out in Bt4.0718 (wide type) which a Bacillus thuringiensis strain screened in our laboratory, using endonuclease I-SceI mediated unmarked gene replacement method. Deletion of Hsp20 resulted in decrease in both sporulation and ICPs production. Bt4-∆hsp20 cells and its ICP did not have significant difference in shape and size but entered the decline phase 2 hrs earlier than the Bt4.0718. In order to find the mechanism that underlies these phenotypes we did proteomic study of differentially expressed proteins (DEPs). In Bt4-∆hsp20 cells 11 DEPs were upregulated and 184 DEPs downregulated. These affected DEPs are involved in multiple metabolic pathways: (1) six DEPs (two upregulated and four downregulated) are directly related to the sporulation and ICPs synthesis; (2) supply of amino acids including amino acid synthesis and protein recycling; (3) the energy supplementation (the tricarboxylic acid cycle and glycolysis); (4) purine metabolism and mRNA stability. These results suggest that hsp20 may be critical in maintaining the homeostasis of Bacillus thuringiensis during the production of spores and ICPs and could provide new sight into the sporulation and ICPs formation in B. thuringiensis.